2018
DOI: 10.3389/fimmu.2018.01185
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Immunity Is Controlled by Tetraspanin Proteins

Abstract: Antitumor immunity is shaped by the different types of immune cells that are present in the tumor microenvironment (TME). In particular, environmental signals (for instance, soluble factors or cell–cell contact) transmitted through the plasma membrane determine whether immune cells are activated or inhibited. Tetraspanin proteins are emerging as central building blocks of the plasma membrane by their capacity to cluster immune receptors, enzymes, and signaling molecules into the tetraspanin web. Whereas some t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 99 publications
1
40
0
Order By: Relevance
“…Tetraspanins control several aspects of anti-tumour immunity [164], but their role in DC migration from the tumour to the lymph nodes and vice versa has not been extensively addressed. One study reported increased tumour growth in Cd37 knock-out mice [133].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetraspanins control several aspects of anti-tumour immunity [164], but their role in DC migration from the tumour to the lymph nodes and vice versa has not been extensively addressed. One study reported increased tumour growth in Cd37 knock-out mice [133].…”
Section: Discussionmentioning
confidence: 99%
“…This was caused by an impaired T cell-driven anti-tumour immune response due to migration failure of CD37-deficient DCs. Further research on the role of tetraspanins in controlling protein expression and DC signalling may enable the discovery of therapeutic strategies targeting tetraspanins to promote DC migration [164]. In conclusion, studies modulating DC migration in cancer are necessary to determine if this strategy, potentially in combination with current therapies, will improve anti-cancer immunity.…”
Section: Discussionmentioning
confidence: 99%
“…CD53 promotes B cell receptor-dependent protein kinase C signalling (46), and increases tumour growth in Cd53 -/mice (47). Patients with low CD53 expression levels were found to have a poor prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…These protein superfamilies, together with a wide variety of transmembrane and cytosolic proteins, mediate the organization of tetraspanin-enriched microdomains (TEMS) in the plasma membrane and the biogenesis of exosomes [42,43]. Tetraspanins CD9, CD63, CD81, CD82 and CD151 are widely distributed among the different cell types, while others, such as Tssc6 CD37 and CD53, are restricted to specific tissues [44]. Exosome release by dendritic cells generated from CD9 knockout mice has been demonstrated to be lower than that from wild-type [45].…”
Section: Exosome Biogenesismentioning
confidence: 99%